(3QSGdI aj GdeDfK hGdePcQ GdSeGYjs
(3ChdgG (B:s
(3GdeDfK GdPj jQhj QhGjI hdG jLhR JPcjQg HhLg(B: (3GdYjf hGdCPf hGdcHO, hGdcQT hGdaMK hGdaNP s
(3BNQgG (B:s
(3hcd LeY Hjfg hHjf hGMOI GdgGA aJPcjQg hJCfjKg LGFQ hGddg CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B137 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT (B- (3HJfg (B(2943) s
Keywords: (3GdfMhs